Alternation between short‐ and long photoperiod reveals hypothalamic gene regulation linked to seasonal body weight changes in Djungarian hamsters (Phodopus sungorus). (2nd July 2017) - Bank, J. H. H.; Wilson, D.; Rijntjes, E.; Barrett, P.; Herwig, A.
Abstract : Djungarian hamsters are able to reduce their body weight by more than 30% in anticipation of the winter season. This particular adaptation to extreme environmental conditions is primarily driven by a natural reduction in day length and conserved under laboratory conditions. We used this animal model to investigate hypothalamic gene expression linked to body weight regulation behind this physiological phenomenon. After an initial collective short photoperiod (SP) adaptation for 14 weeks from a preceding long photoperiod (LP), hamsters were re‐exposed to LP for either 6 or 14 weeks, followed by a second re‐exposure to SP for 8 weeks. Our data showed that re‐exposure to LP led to an increase in body weight. In the hypothalamus Dio2, Vimentin, Crbp1 and Grp50 expression increased, whereas expression of Dio3, Mct8 and Srif decreased. The changes in body weight and gene expression were reversible in most hamsters after a further re‐exposure to SP following 6 or 14 weeks in LP. Interestingly, after 14 weeks in LP, body weight loss was pronounced in six hamsters re‐exposed to SP, but five hamsters did not respond. In nonresponding hamsters, a different gene expression pattern was manifested, with the exception of Dio2, which was reduced not only in SP re‐exposed hamsters, but also in hamsters maintained in LP. Taken together, these data suggest that body weight regulation appears to be tightly linked to a co‐ordinated regulation of several genes in the hypothalamus, including those involved in thyroid hormone metabolism.